Migration and integration processes in Portugal - Vieira, Ricardo (2019)
Migration is generally described as a process that is nationally specific and that have features common to several countries. This has been shown by several authors through comparative research that compares the migration process of the same immigrant group to several countries (among others, Engbersen, Snel, & de Boom, 2010) or which scrutinises the migration realities of different countries (Zimmermann, 2005). Most of these studies are about geographically near countries, which are part of the same political system (the EU), and that have an established (albeit differentiated) welfare system. These proximities (geographical, but also political and social) allowed the authors of these studies to conceptualise the existence of several migration models or regimes: the southern European model (Baldwin-Edwards, 2012), the Iberian model of Migration (Malheiros, 2012); the intra-EU mobility regime (Engbersen et al., 2017). These migratory regimes are intertwined by migrant integration models or by different approaches to increasingly diverse populations. Although these are often identified as ‘national models of integration’, they do not fail to integrate the developments that have been recorded in the last decades in the international contexts in which the countries are inserted. Throughout the present text, the Portuguese experience in dealing with immigrant integration is used to reflect on the development of intercultural policies and practices, and on the role of intercultural mediation. The article is structured in the following way: in the introductory section we will review the discussion on interculturalism; in a second section the Portuguese immigration context will be presented; in a third section the integration of immigrants in the country will be analysed, given special attention to the development of policies that support immigrants’ integration process. In the fourth section, the role of intercultural mediation for the integration of immigrants will be considered.